Network Pharmacology Approaches to Myocardial Infarction Reperfusion Injury: Exploring Mechanisms, Pathophysiology, and Novel Therapies - Joy Das; Ashok Kumar Sah; Ranjay Kumar Choudhary; Rabab H. Elshaikh; Utpal Bhui; Shreya Chowdhury; Anass M. Abbas; Manar G. Shalabi; Nadeem Ahmad Siddique; Raji Rubayyi Alshammari; Navjyot Trivedi; Khoula Salim Ali Buwaiqi; et al. (Biomedicines, 2025)
Myocardial infarction (MI) remains a leading cause of morbidity and mortality worldwide. While timely reperfusion therapies such as percutaneous coronary intervention (PCI) and thrombolysis are essential for salvaging ischemic myocardium, they can paradoxically exacerbate tissue injury through a process known as myocardial infarction reperfusion injury (MIRI). MIRI can contribute to up to 50% of the final infarct size, significantly diminishing the benefits of revascularization and leading to worsened cardiac outcomes. The pathophysiology of MIRI involves complex, interrelated mechanisms including oxidative stress, calcium overload, mitochondrial dysfunction, inflammatory responses, apoptosis, and dysregulated autophagy. Post-reperfusion recovery is further complicated by structural and functional abnormalities such as microvascular obstruction, endothelial dysfunction, and myocardial stunning. Clinically, distinguishing reperfusion injury from ischemic damage is challenging and often requires the use of sensitive biomarkers, such as cardiac troponins, alongside advanced imaging modalities. Although a range of pharmacological (e.g., antioxidants, calcium channel blockers, mitochondrial stabilizers, anti-inflammatory agents) and non-pharmacological (e.g., hypothermia, gene therapy, stem cell-based therapies) interventions have shown promise in preclinical studies, their clinical translation remains limited. This is largely due to the multifactorial and dynamic nature of MIRI. In this context, network pharmacology offers a systems-level approach to understanding the complex biological interactions involved in MIRI, facilitating the identification of multi-target therapeutic strategies. Integrating network pharmacology with omics technologies and precision medicine holds potential for advancing cardioprotective therapies. This review provides a comprehensive analysis of the molecular mechanisms underlying MIRI, examines the current clinical challenges, and explores emerging therapeutic strategies. Emphasis is placed on bridging the translational gap through validated, multi-target approaches and large-scale, multicenter clinical trials. Ultimately, this work aims to support the development of innovative and effective interventions for improving outcomes in patients with myocardial infarction.